FRUSTRATION IN MOBILE LEGENDS AND VERBAL AGGRESSION AMONG SMAN 12 STUDENTS - Salsabela, Ghina; Farial, Farial; Aminah, Aminah (PT Altin Riset Publishing, 2025)
This study aims to identify the relationship between frustration experienced while playing Mobile Legends online games and verbal aggression among students at SMAN 12 Banjarmasin. This study employs a quantitative correlational approach, with the population consisting of 10th-grade students at SMAN 12 Banjarmasin, and a sample size of 90 participants. The sample was selected from students who met the criteria of playing the online game Mobile Legends. Data collection was conducted using a Likert scale for the variables of frustration, discomfort, and verbal aggression. Data analysis in this study used Pearson product-moment correlation analysis. The results showed a significant relationship between frustration and verbal aggression, with a correlation coefficient of ????hitung = 0.377 and a significance value of ???? = 0.000. This indicates that an increase in frustration is associated with an increase in verbal aggression among students, and the null hypothesis (Ha) is accepted in this study. Further research is recommended to expand the scope of the study by considering other variables that may influence verbal aggression.